Methodology of organization of scientific research - Moroz, Volodymyr M.; Buka, Stanislav; Moroz, Svitlana A.; Trush, Oleksandr Olehovych; Moroz, Oleksandr ("Novyi Svit – 2000", 2024)
The manual offers an exhaustive in its content and logical in the sequence of presentation model of mastering the problematics of theoretical and methodological basics of development and holding a research. The manual conceptualizes the views of domestic and foreign scientists on the theory and practice of the researcher's use of scientific approaches, principles and methods in the system of methodological support of scientific-research work. In addition, the manual highlights the problematics of the place and role of science in assuring the mankind's socio-political and socio-economic development, as well as the issues of formulating the content of the basic categories of the methodology for organizing scientific researches. The manual will be useful for the higher education applicants at the second (master's) and third (educational and scientific) levels of its acquisition in the specialties 054 “Sociology” and 281 “Public Administration and Governance”, as well as for higher education applicants in other specialties.
Keywords: manual; scientific research; scientific research organization; methodology’s functions; classification of scientific researches